Harmonized Commodity Description and Coding System (World Customs Organization BrusselsBE, 2005)
Contains the texts of the International Convention on the Harmonized Commodity Description and Coding System approved by the Customs Co-operation Council on 14 June 1983, the Protocol of Amendment to that Convention and the Council's recommendations concerning the Amendment of the Harmonized System. Includes also, the text of the Nomenclature established under the Convention amended as at 1 January 2007.
On permanent loan to Single Market & Economy (Mr. N. Breedy). 4th Edition withdrawn and replaced with 5th Edition, 2012.